(untitled) (Research, Society and Development, 2020)
Carbofuran (2.3-dihydro-2.2-dimethyl-benzofuranyl-N-methylcarbamate) is an insecticide belonging to the group of carbamates, widely used in pest control in crops with great commercial value, bioaccumulative and extremely toxic to the environment. An alternative to treat areas contaminated with pesticides is bioremediation, which consists of using microorganisms or their enzymes to remove persistent chemical compounds. Thus, the objective of this study was to determine the biodegradation of carbofuran, using the fungus Syncephalastrum racemosum, by evaluating fungal tolerance, enzymatic activity and quantifying residues by UV-Visible spectrophotometry. The results obtained showed that S. racemosum presented best biodegradation capacity at 15 µg mL-1carbofuran concentration (93.02%), with IVCM values of 21.95 cm day-1, laccase (0.712 U mL-1) and lignin peroxidase (0.005 U mL-1), after 168 h incubation. Thus, the degradation rate in the 25 to 100 µg mL-1 range showed values of 12.66 to 75.58%, respectively. Based on these results, the fungus has great potential for use in the bioremediation, minimizing the impacts of this pesticide on the environment.